2016
DOI: 10.12669/pjms.325.10429
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and clinical features of Hepatitis C Virus(HCV) in epidemic areas of Interior Sindh, Pakistan

Abstract: Objective:Highly variable genome of HCV and high prevalence in many geographical areas made it necessary to conduct local population studies. This study has been conducted to show HCV parameters along with clinical features in the local population of interior Sindh, province of Pakistan.Methods:Present study was conducted in from August 2010 to November 2015 in the rural areas of Sindh, Pakistan. All the 31560 screened samples selected for the study were tested by second Generation Enzyme Linked Immunosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…HCV genotyping data of Sindhi patients published in 2014 resemble our findings (12). These analyses demonstrate 3a as most prevalent genotype, followed by untypable, 3b, and 1a in decreasing order (12,24). Conclusions drawn by Shaikh et al were in contrast with the analysis in this study, which showed 3a (50.8%) as most prevalent, and exceptionally high frequency of untypable (47%) was observed, followed by 2a (1.6%).…”
Section: Hcv Genotype Prevalence In Pakistan 409contrasting
confidence: 96%
“…HCV genotyping data of Sindhi patients published in 2014 resemble our findings (12). These analyses demonstrate 3a as most prevalent genotype, followed by untypable, 3b, and 1a in decreasing order (12,24). Conclusions drawn by Shaikh et al were in contrast with the analysis in this study, which showed 3a (50.8%) as most prevalent, and exceptionally high frequency of untypable (47%) was observed, followed by 2a (1.6%).…”
Section: Hcv Genotype Prevalence In Pakistan 409contrasting
confidence: 96%
“…Manzor 2016 reported higher prevalence of Hepatitis C among males as compared to females with the age range from 18 to 65 years (Bhatti and Manzoor 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A few studies conducted in Karachi show dual HBV-HCV prevalence as 0.11% in household children26, 1.3% in viral hepatitis patients27 and 3.1% in patients of hepatitis B28. In one community based study Bhatti and Manzoor described 2.5% dual HBV-HCV prevalence in rural areas of Sindh29. A previous study by Junejo et al presented 3.9% co-prevalence of HBsAg and anti-HCV infection in the ocular patients of Hyderabad30.…”
Section: Introductionmentioning
confidence: 96%